Control biopolítico en el sistema de salud colombiano: Ley 100 de 1993. (2020)
This article presents the results of an investigation project whose aim was to determine the presence of biopolitical control elements in the formulation of the Colombian health system, regulated by Law 100 of 1993. Having in mind that all the population makes part of the health system, a constant and transdisciplinary analysis is necessary, to study the suitability of its operation, its service conditions, and the essential improvements to its actualization and maintenance. Thus, qualitative research was realized, prioritizing the documentary sources that allowed the correlation between context analyses, theoretical references, and the normativity of the health model. The results showed legal grey areas and legal loopholes in the surveillance state of the private participants on the health system, which have enabled and promoted the control over the lives of the citizens who make use of the health services.